From essential basic understanding to clinical application – biological, physical and pathophysiological principles of (low-dose) radiotherapy in benign diseases - Deloch, Lisa; Steike, David Rene; Pascher, Felix; Thole, Anne-Marie; Shariff, Maya; Kriz, Jan; Sonnhoff, Mathias; Blach, Robert; Montero, Angel; Paulsen, Friedrich; Socher, Eileen; Ordonez, Silvia Gomez; et al. (Frontiers in Immunology, 2025)
Low dose radiotherapy (LDRT) is a radiation technique in the treatment of benign conditions to relieve symptoms and improve mobility and pain with minimal overall side effects. There are many reports describing the use of LDRT in the treatment of osteoarthritis (OA), tendinitis and hyperproliferative disorders. The targeted diseases are complex and multifactorial, characterized by inflammation, cellular alterations, and tissue degeneration, affecting millions of people worldwide with increasing prevalence due to aging populations. However, an understanding of the pathophysiological mechanisms as well as the underlying biological and physical mechanisms is important for the clinical-practical application, as a foundation for empirical clinical studies and state-of-the-art patient treatment. In this review, we provide an overview of the broad use of LDRT in the treatment of benign diseases with well-described and illustrated overviews of the pathomechanisms of OA, tendinitis, bursitis, benign fibromatoses and hyperproliferative diseases. The biological, physical, and molecular mechanisms behind it are also described. We further provide a broad overview of studies as well as current discussions of the therapy such as risk assessment, treatment frequency and dosage, along with future perspectives to improve clinical application overall. Taken together, this review illustrates the multifaceted application of (LD)RT, emphasizing that each disease requires a unique treatment approach due to the wide variation in pathology, biological mechanisms, target volumes, and organs at risk, but it also highlights the need for well-designed (placebo)-controlled studies in a range of indications.